Pengaruh Literasi Keuangan Dan Demografi Terhadap Keputusan Investasi Pegawai Dinas Kependudukan dan Pencatatan Sipil Kabupaten Buleleng - Anggreni, Kadek Vina; I Nyoman Sujana (Universitas Pendidikan Ganesha, 2025)
This study aims to analyze the influence of financial literacy and demographic factors on investment decisions of employees of the Population and Civil Registration Service of Buleleng Regency. The approach used is quantitative with a sample size of 30 people selected through purposive sampling techniques. Data were collected through questionnaires and documentation, then analyzed using multiple linear regression. Before the multiple linear regression analysis was carried out, classical assumption tests were first carried out such as normality, multicollinearity, and heteroscedasticity tests. The results of the study showed that: (1) Partially, financial literacy has no significant effect on investment decisions, (2) Partially, demographically, it has a positive and significant effect on investment decisions, and (3) Simultaneously, financial literacy and demographics together have a positive and significant effect on investment decisions. These findings indicate that demographic factors play an important role in driving investment decisions, as well as the importance of increasing financial literacy to support wiser investment decision-making in the future.